1989
DOI: 10.1063/1.456554
|View full text |Cite
|
Sign up to set email alerts
|

Chemisorption and thermal decomposition of ethylene on Pd(110): Electron energy loss spectroscopy, low-energy electron diffraction, and thermal desorption spectroscopy studies

Abstract: The adsorbed state of ethylene on Pd(110) at 90 K and its thermal decomposition in the temperature region between 90 and 600 K have been studied by the use of high resolution electron energy loss spectroscopy (EELS), low-energy electron diffraction (LEED), and thermal desorption spectroscopy (TDS). At 90 K, ethylene is π bonded to the Pd(110) surface and is adsorbed almost disorderedly. The c(2×2)-C2H4 patches are formed near the saturation coverage (which corresponds to 0.58 C2H4 molecule per surface Pd atom)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 43 publications
3
53
0
Order By: Relevance
“…In some cases the change in the cluster size by one metal atom can be accompanied by a large change in the reactivity, and curves like Figure 5 were often found in experiments. We notice that for Pd [3][4][5] clusters, which collapse under the di-σ adsorption, the best adsorption mode is π, whereas the Pd 2 and Pd 6 , which give π and di-σ distortions of the same magnitude, the di-σ adsorption is more favorable.…”
Section: Adsorption Of Ethylene On Pd N (N ) 3-6) Clustersmentioning
confidence: 96%
See 2 more Smart Citations
“…In some cases the change in the cluster size by one metal atom can be accompanied by a large change in the reactivity, and curves like Figure 5 were often found in experiments. We notice that for Pd [3][4][5] clusters, which collapse under the di-σ adsorption, the best adsorption mode is π, whereas the Pd 2 and Pd 6 , which give π and di-σ distortions of the same magnitude, the di-σ adsorption is more favorable.…”
Section: Adsorption Of Ethylene On Pd N (N ) 3-6) Clustersmentioning
confidence: 96%
“…However, HREELS experiments support a π adsorption on Pd(111) 2 and Pd(110), 3 whereas for Pd(100) 1 both π and di-σ modes were observed. Table 6 also shows the spin state of the C 2 H 4 Pd n complexes.…”
Section: Adsorption Of Ethylene On Pd N (N ) 3-6) Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactions of ethene with metal surfaces have been investigated on both single crystals and supported catalysts (see reviews of Zaera [6], and Sheppard and De La Cruz [7,8]). As Pd catalysts typically show high activities and selectivities, a considerable research effort has been devoted to studying surface reactions on Pd, employing infrared reflection absorption spectroscopy (IRAS), temperature-programmed desorption (TPD), high-resolution electron (and photoelectron) spectroscopy (HREELS, PES), and ab initio calculations [9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental studies of the adsorption of ethylene on palladium surfaces have been found on the literature [47][48][49]. According with these studies on the (111) and (110) surfaces, the ethylene molecule adsorbs preferably in the In the only known experimental studies on the adsorption of on a Pd(l00) surface, at low temperatures, Stuve et al [64,65] using TPRS and EELS concluded that both and forms are stable and coexist on this surface at 80 K. Table 8 lists the results obtained for adsorbed on a Pd(l00) surface on the and adsorption modes.…”
Section: 123mentioning
confidence: 99%